The Law of Passorong Ownership in Mandar Community Marriage, Majene Regency: A Comparison Study of Islamic Law and Positive Law - Supriadi, Supriadi; Ridwan P, Muh. (Faculty of Sharia and Islamic Law Institut Agama Islam Negeri Bone, 2023)
The presence of Passorong in the Mandar ethnicity of Majene Regency is a gift of wealth from the prospective husband to his prospective wife to enter into a marriage. Passorong in terms is similar to dowry in Islamic law, which is a gift from the groom to the bride. This study is a field study with a qualitative descriptive research type. The source of data in this research is the Office of Religious Affairs in Majene Regency. The approach used consists of normative theological, juridical, sociological, anthropological, and philosophical approaches. Methods of data collection obtained directly from the field using observation techniques, interviews, and documentation. Data processing using deductive techniques with qualitative descriptive analysis. The results of the study show that the mechanism for giving passorong in the marriage of the Mandar community in Majene Regency is usually in the form of objects that have value or benefits. The mechanism for giving Passorong goes through several stages before the marriage contract, namely an agreement is made after the proposal process takes place, such as mattandajari and maccanring. Passorong objects given by prospective husbands to prospective wives vary, but are usually in the form of gold and land and coconut trees accompanied by land, real or converted in rupiah. The practice of giving a passorong is in line with Islamic law, giving a passorong is classified as a musamma dowry, because it determines the amount and type of item that is used as a dowry at the time the marriage contract takes place. While in positive law, legally speaking a certificate has not been issued in the name of the wife, in the Law on Basic Agrarian Regulations and Government Regulation Number 24 of 1997 concerning land registration that a passorong is in the form of land if to obtain eigendom rights over land must be certified in the name of the wife .